Ethnicity and gender in Sab (1841) by Gertrudis Gómez de Avellaneda - Zevallos, Johnny (2018)
The Hispanic-American novels of the 19th century have as their central theme the representation of national characters related to the interpretation of European readers. For this reason, they respond to Eurocentric patriarchal models that exclude foreign biotypes. In this sense, the novel Sab, by the Cuban Gertrudis Gómez de Avellaneda, published in years when the island was one of the remnants of the Spanish empire, incorporates an exotic vision of non-European characters, considering them as agents of an eminent modernization and uses a slave as a prototype of subalternity as opposed to the civilized white masters. Therefore, we propose to demonstrate how the story maintains the patriarchal and patrimonial canons of the Cuban nation by legitimizing white male hegemony to favor the afrodescendant subalternity.